Toward a systemic plant physiology - Souza, Gustavo M.; Prado, Carlos H. B. A.; Ribeiro, Rafael V.; Barbosa, Joao Paulo R. A. D.; Goncalves, Antonio Natal; Habermann, Gustavo [UNESP] (Brazilian Soc Plant Physiology, 2016)
This manuscript brings a critical reflection on the epistemological foundations of the science of plant physiology. We discuss the limits of the reductionist view of the science, indicating new epistemological possibilities to plant physiology, specially based on General System Theory and Complex System paradigm, and the further implications of this major science to the human future.
Keywords: Philosophy of plant physiology; Plant cognition; Plant science; System biology